Development of a Final Project Guidance Service Model for Students through a Mobile Application - Yusuf, Farida; Purnamawati, Purnamawati; Riana, TM (Cita konsultindo, 2024)
The implementation of the final project mentoring service model for students through a mobile application is designed to facilitate the final project mentoring process for students, thereby increasing the number of students who complete their studies on time. The objectives of this research are (1) to analyze the needs for a final project guidance service model for students through a mobile application; (2) to design a final project guidance service model for students through a mobile application; (3) to build a final project guidance service model for students through a mobile application; (4) to determine the validity of the final project guidance service model for students through a mobile application; (5) to determine the practicality of the final project guidance service model for students through a mobile application; (6) to determine the effectiveness of the final project guidance service model for students through a mobile application; and (7) to determine the results of the system testing of the final project guidance service model for students through a mobile application. The type of research is Research & Development. (R&D). Data collection techniques used interview, observation, and questionnaire methods. Data analysis techniques used validity analysis, practicality analysis, and effectiveness analysis. System testing techniques used were black box and user acceptance testing. The results of this study indicate that the model of thesis supervision services for students through this mobile application is feasible to use, making the thesis supervision process for students more efficient and effective.